Laminated nonwoven fabric for liquid-impregnated skin covering sheet and manufacturing method thereof, liquid-impregnated skin covering sheet, and face mask

JP7610927B2Active Publication Date: 2025-01-09DAIWA BOSEKI KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020063841
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-31
Publication Date
2025-01-09
Estimated Expiration
2040-03-31

AI Technical Summary

Benefits of technology

【0008】 本開示の液体含浸皮膚被覆シート用積層不織布は、撥水性セルロース繊維が皮膚と接触する面に存在するため、良好な密着性を示すとともに、セルロース繊維に由来する良好な触感および風合いを有する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610927000004
    Figure 0007610927000004
  • Figure 0007610927000001
    Figure 0007610927000001
  • Figure 0007610927000002
    Figure 0007610927000002
Patent Text Reader

Abstract

To provide a liquid impregnated skin covering sheet which has excellent adhesion to skin and good touch of feeling.SOLUTION: There is provided a laminated nonwoven fabric for liquid impregnated skin covering sheet in which a first fiber layer and a second fiber layer laminated on the first fiber layer are integrated. Based on the total mass of the first fiber layer, the first fiber layer comprises: a water-repellent cellulose fiber of 30 mass% or more and 80 mass% or less; and a hydrophilic cellulose fiber of 20 mass% or more and 70 mass% or less. Based on the total mass of the second fiber layer, the second fiber layer comprises: a hydrophilic cellulose fiber of 50 mass% or more; and a water-repellent cellulose fiber of 0 mass% or more and 20 mass% or less. The first fiber layer and the second fiber layer are integrated by interlacing fibers of the fiber layers, and the first fiber layer is used in contact with skin.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a laminated nonwoven fabric that serves as a substrate for a liquid-impregnated skin application sheet that is impregnated with a liquid, particularly a cosmetic preparation, and a method for producing the same, as well as a liquid-impregnated skin application sheet and a face mask that use the nonwoven fabric. [Background technology]

[0002] Various liquid-impregnated sheets have been proposed and put into practical use, which are used to cover the skin of a human or animal body and to apply a specific substance to the skin of a human or animal body. Specific examples include liquid-impregnated skin covering sheets (face masks and keratin care sheets used on the heels, elbows, knees, etc.) impregnated with a liquid (e.g., cosmetics) containing an active ingredient. Nonwoven fabrics are generally used as the substrate for liquid-impregnated skin covering sheets. Since liquid-impregnated skin covering sheets are often used in contact with the skin for a relatively long time, various nonwoven fabrics have been proposed as the substrate in terms of adhesion, liquid release, touch, convenience, etc. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2006 / 016601 Brochure [Patent Document 2] JP 2016-98464 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present disclosure is to provide a liquid-impregnated skin application sheet that exhibits good adhesion to the skin when impregnated with a liquid, and whose surface in contact with the skin provides a good tactile feel derived from cellulose fibers. [Means for solving the problem]

[0005] The present disclosure provides a laminated nonwoven fabric for a liquid-impregnated skin application sheet, comprising a first fiber layer and a second fiber layer laminated on the first fiber layer, the laminated nonwoven fabric comprising: the first fiber layer contains, based on the total mass of the first fiber layer, 30% by mass or more and 80% by mass or less of water-repellent cellulose fibers and 20% by mass or more and 70% by mass or less of hydrophilic cellulose fibers; the second fiber layer contains hydrophilic fibers in an amount of 50% by mass or more and water-repellent cellulosic fibers in an amount of 0% by mass or more and 20% by mass or less, based on the total mass of the second fiber layer; the first fiber layer and the second fiber layer are integrated by entanglement of the fibers, The first fiber layer is used by contacting it with the skin. Provided is a laminated nonwoven fabric for use as a liquid-impregnated skin covering sheet.

[0006] The present disclosure also provides a laminated nonwoven fabric for a liquid-impregnated skin application sheet, comprising a first fiber layer and a second fiber layer laminated on the first fiber layer, the laminated nonwoven fabric comprising: the first fibrous layer comprises water-repellent cellulose fibers and hydrophilic cellulose fibers; the second fibrous layer comprises hydrophilic fibers; the first fiber layer and the second fiber layer are integrated by entanglement of the fibers, the spot absorptivity on the surface of the first fiber layer is 35% or more; the spot absorption time on the surface of the first fiber layer is 0.6 seconds or more; the spot absorption time on the surface of the second fiber layer is 0.1 seconds or less; The first fiber layer is used by contacting it with the skin. Provided is a laminated nonwoven fabric for use as a liquid-impregnated skin covering sheet.

[0007] The present disclosure also provides a method for producing a first fiber web comprising, based on the total weight of the first fiber web, 30% by weight or more and 80% by weight or less of water-repellent cellulosic fibers and 20% by weight or more and 70% by weight or less of hydrophilic cellulosic fibers; preparing a second fiber web containing 50% by mass or more of hydrophilic fibers and 0% by mass or more and 20% by mass or less of water-repellent cellulosic fibers based on the total mass of the second fiber web; overlapping the first fiber web and the second fiber web to produce a laminated fiber web; subjecting the laminated fiber web to an entanglement treatment using a high-pressure fluid flow to entangle the fibers. Including, The present invention provides a method for producing a laminated nonwoven fabric for a liquid-impregnated skin application sheet, in which the first fiber web serves as a first fiber layer and the second fiber web serves as a second fiber layer, and the first fiber layer is used by contacting the skin. Effect of the Invention

[0008] The liquid-impregnated laminated nonwoven fabric for skin application sheets of the present disclosure has good adhesion because the water-repellent cellulose fibers are present on the surface that comes into contact with the skin, and has a good feel and texture derived from the cellulose fibers. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a schematic diagram showing the contact angle between the surface of a nonwoven fabric and water. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] (How this embodiment came about) As described above, various fibers and various configurations have been proposed as the substrate of the liquid-impregnated skin application sheet (hereinafter, also simply referred to as "sheet"). For example, Patent Document 1 discloses a cosmetic-impregnated skin application sheet in which an ultrafine fiber layer containing 10% by mass or more of ultrafine fibers with a fineness of 0.5 dtex or less is positioned on one or both surfaces of a hydrophilic fiber layer containing 50% by mass or more of hydrophilic fibers, and the hydrophilic fiber layer and the ultrafine fiber layer are integrated, with the ultrafine fiber layer being the surface that comes into contact with the skin. In the sheet described in Patent Document 1, the ultrafine fiber layer provides a dense and smooth surface, and the cosmetic easily forms a thin film between the skin and the sheet. Therefore, the sheet described in Patent Document 1 has a good feel due to the dense and smooth surface of the ultrafine fiber layer, and the irritation to the skin is reduced due to the liquid film interposed between the skin and the sheet. All of the ultrafine fibers exemplified in Patent Document 1 are synthetic fibers.

[0011] The sheet described in Patent Document 2 includes a first fiber layer containing 50% by mass or more of hydrophilic fibers and a second fiber layer containing 50% by mass or more of hydrophobic fibers that are more hydrophobic than the hydrophilic fibers contained in the first fiber layer, the hydrophobic fiber layer has a fineness of 1.2 dtex or more, and contains two or more types of fibers with different hydrophobicities as the hydrophobic fibers, and the first fiber layer is used by contacting the skin. According to the sheet described in Patent Document 2, the impregnated liquid is easily retained on the skin, and the liquid exerts a better adhesion effect and moisturizing effect.

[0012] The sheet of Patent Document 1 has a surface that comes into contact with the skin made of ultrafine synthetic fibers, while the sheet of Patent Document 2 has a surface that comes into contact with the skin made of hydrophilic fibers, and by utilizing the characteristics of each fiber, they achieve low irritation or good adhesion. However, since liquid-impregnated skin covering sheets are used by various users of different ages and constitutions, a texture that is favorable for one user may be unpleasant for another user. In addition, the type of impregnated liquid varies depending on the effect that the sheet provides (for example, in the case of a face mask, moisturizing, whitening, or suppression of sagging skin, etc.), and the texture of the sheet may change when the liquid to be impregnated changes, so the composition of the sheet may need to be changed depending on the type of liquid.

[0013] Additionally, due to increased environmental awareness and / or a preference for natural materials, some users prefer sheets that contain more natural fibers or fibers made from naturally derived materials rather than products that contain a large amount of synthetic fibers.

[0014] Unlike Patent Document 2 and the like, the present inventors attempted to use the surface of a fiber layer containing water-repellent fibers as the surface that comes into contact with the skin, instead of the surface of a fiber layer containing a large amount of hydrophilic fibers, and to use cellulose fibers as the water-repellent fibers. Although synthetic fibers (particularly fibers made of polyethylene terephthalate) are available as water-repellent fibers, the use of water-repellent cellulose fibers was attempted for users who do not like synthetic fibers. However, when a single-layer nonwoven fabric was manufactured using water-repellent cellulose fibers or a combination of water-repellent cellulose fibers and hydrophilic cellulose fibers, the mechanical strength of the nonwoven fabric was reduced. Therefore, when adhesive fibers were mixed to bond the fibers together in order to increase the mechanical strength, the texture became hard.

[0015] The inventors attempted to construct a structure in which the surface in contact with the skin is the surface of a fiber layer containing water-repellent cellulose fibers and hydrophilic cellulose fibers, and the fiber layer contains hydrophilic fibers and does not contain water-repellent cellulose fibers or, if it does contain water-repellent cellulose fibers, the proportion of water-repellent cellulose fibers is 20 mass % or less, and the fibers are integrated by entangling with each other. As a result, a nonwoven fabric having excellent adhesion and relatively high mechanical strength, and suitable as a substrate for a liquid-impregnated skin application sheet, was obtained. Hereinafter, the fibers constituting the nonwoven fabric of this embodiment will first be described.

[0016] (Water-repellent cellulose fiber) Although cellulose fibers are inherently hydrophilic, in this embodiment, cellulose fibers to which water repellency has been artificially imparted are called "water-repellent cellulose fibers" and are used. There are no particular limitations on the type of cellulose fibers. The following cellulose fibers are included: (1) Natural fibers derived from plants, such as cotton, flax, flax, ramie, jute, banana, bamboo, kenaf, shell ginger, hemp, and kapok; (2) regenerated fibers such as viscose-processed rayon and polynosic rayon, cupra-processed cuprammonium-processed cupramide, and solvent-spinning-processed Tencel® and Lyocell®; (3) Cellulose fibers obtained by melt spinning; (4) Semi-synthetic fibers such as acetate fibers; and (5) Pulp, such as mechanical pulp, recycled pulp and chemical pulp

[0017] The water-repellent cellulose fibers may be those obtained by attaching a water-repellent agent to these cellulose fibers to impart water repellency. Alternatively, the water-repellent cellulose fibers may be obtained by a method in which a specific compound is mixed into a spinning solution to spin regenerated fibers, and then a specific water-repellent agent is applied to the regenerated fibers to cause bonding between the specific compound and the water-repellent agent, thereby imparting water repellency. Water-repellent regenerated cellulose fibers obtained by such a method are disclosed, for example, in JP 2019-65443 A.

[0018] As water-repellent cellulose fibers, for example, Ecorepellent (trade name, water-repellent viscose rayon) manufactured by Daiwabo Rayon Co., Ltd. and Olea (trade name, water-repellent viscose rayon) manufactured by Kelheim Fibres GmbH are commercially available. In this embodiment, these water-repellent cellulose fibers may be used. In particular, Ecorepellent (trade name) is preferably used because it exhibits high water repellency, has highly durable water repellency, and is less likely to decrease in water repellency even when subjected to, for example, hydroentanglement treatment.

[0019] The fineness of the water-repellent cellulose fibers may be, for example, 0.6 dtex or more and 3.3 dtex or less, particularly 1.0 dtex or more and 2.5 dtex or less, and more particularly 1.4 dtex or more and 2.0 dtex or less. If the fineness of the water-repellent cellulose fibers is too small, the voids in the first fiber layer become small, so that the nonwoven fabric is difficult to retain liquid, and if it is too large, the touch of the nonwoven fabric may be deteriorated. The fineness of the water-repellent cellulose fibers is not limited to these ranges. In particular, when using natural fibers, since it is difficult to adjust the fineness, fibers with fineness outside the above ranges may be used.

[0020] The fiber length of the water-repellent cellulose fibers is not particularly limited and may be appropriately selected depending on the manufacturing method of the laminated nonwoven fabric. For example, when the first fiber layer is manufactured by preparing a card web in the manufacturing of the laminated nonwoven fabric, the water-repellent cellulose fibers may be short fibers. The fiber length of the short fibers may be, for example, 20 mm or more and 100 mm or less, particularly 28 mm or more and 75 mm or less, and more particularly 30 mm or more and 65 mm or less. Alternatively, when the first fiber layer is manufactured by an air-laying method, the fiber length may be, for example, 2 mm or more and 20 mm or less. In this embodiment, a plurality of water-repellent cellulose fibers having different properties in one or more of material, fiber length, and fineness may be used.

[0021] In this embodiment, the water repellency of the water-repellent cellulose fiber can be evaluated, for example, by measuring the water immersion time by the following method. (1) Take 1g of raw cotton and lightly roll it into a ball. (2) Pour 300 mL of water into a 300 mL beaker and gently drop the sample from a height of 1 cm above the water surface. The height from the bottom of the beaker to the water surface is 7 cm. (3) Observe the condition of the raw cotton for 10 minutes and measure the time it takes for the raw cotton to reach the bottom of the beaker (immersion time).

[0022] When the immersion time is measured by the above method, if the sample absorbs water but does not sink to the bottom of the beaker after 10 minutes, it is preferably used as a water-repellent cellulose fiber. If the sample does not sink after 10 minutes and floats partially or entirely on the water surface, it is more preferably used as a water-repellent cellulose fiber.

[0023] (hydrophilic cellulose fiber) In this embodiment, a combination of water-repellent cellulose fibers and hydrophilic cellulose fibers is used. The term "hydrophilic cellulose fibers" is used to distinguish them from water-repellent cellulose fibers, and refers to cellulose fibers that are not imparted with water repellency and have inherent hydrophilicity. Therefore, examples of hydrophilic cellulose fibers are as described above with respect to the water-repellent cellulose fibers.

[0024] The hydrophilic cellulose fiber may be a regenerated fiber. Regenerated fibers are preferably used because the fineness of the regenerated fibers can be easily adjusted and the variation is small. Among the regenerated fibers, viscose rayon is particularly preferably used because it is advantageous in terms of cost.

[0025] The fineness of the hydrophilic cellulose fibers may be, for example, 0.2 dtex or more and 3.0 dtex or less, particularly 0.3 dtex or more and 2.2 dtex or less, and more particularly 0.6 dtex or more and 2.0 dtex or less. If the fineness of the hydrophilic cellulose fibers is too small, fiber clumps (neps) are likely to occur in the nonwoven fabric, and if it is too large, the touch of the nonwoven fabric may be deteriorated. The fineness of the hydrophilic cellulose fibers is not limited to these ranges. In particular, when natural fibers are used, those with finenesses outside the above ranges may be used because it is difficult to adjust the fineness.

[0026] The fiber length of the hydrophilic cellulose fibers is not particularly limited and may be appropriately selected depending on the manufacturing method of the laminated nonwoven fabric, etc. The relationship between the manufacturing method of the laminated nonwoven fabric (the method of producing the fiber layer) and the fiber length is as described in relation to the water-repellent cellulose fibers.

[0027] The first fibrous layer may include a plurality of hydrophilic cellulose fibers that are different in one or more of material, fiber length, and fineness.

[0028] The hydrophilic cellulose fiber may be one in which, when the immersion time is measured by the method described in the evaluation method for the water repellency of the water repellency of the water repellency cellulose fiber, the sample reaches the bottom of the beaker within 60 seconds. The hydrophilic cellulose fiber may be one in which, after the sample is dropped on the surface of the water in the beaker, it absorbs water and reaches the bottom within, for example, 50 seconds, particularly within 45 seconds, and more particularly within 30 seconds.

[0029] (hydrophilic fiber) Specifically, the hydrophilic fibers include the hydrophilic cellulose fibers described above, as well as natural fibers other than cellulose fibers (e.g., silk, wool, etc.), synthetic fibers having hydrophilic properties, or hydrophobic synthetic fibers (synthetic fibers with an official moisture regain of less than 5%) that have been subjected to a hydrophilization treatment. Examples of the hydrophilization treatment include corona discharge treatment, sulfonation treatment, graft polymerization treatment, kneading a hydrophilizing agent into the fibers, and application of a durable oil agent. The hydrophilic fibers are preferably the hydrophilic cellulose fibers described above.

[0030] The fineness of the hydrophilic fibers is preferably the same as that of the hydrophilic cellulose fibers described above. The fiber length of the hydrophilic fibers is not particularly limited and may be appropriately selected depending on the manufacturing method of the laminated nonwoven fabric, etc. The relationship between the manufacturing method of the laminated nonwoven fabric (the method of producing the fiber layer) and the fiber length is as described in relation to the water-repellent cellulose fibers. In this embodiment, a plurality of hydrophilic fibers different in one or more of material, fiber length, and fineness may be used.

[0031] The hydrophilic fiber may be one in which, when the immersion time is measured by the method described in the evaluation method for the water repellency of the water-repellent cellulose fiber, the sample reaches the bottom of the beaker within 60 seconds. The hydrophilic fiber may be one in which, after the sample is dropped on the surface of the water in the beaker, it absorbs water and reaches the bottom within, for example, 50 seconds, particularly within 45 seconds, and more particularly within 30 seconds.

[0032] (Adhesive Fiber) The laminated nonwoven fabric of this embodiment may contain adhesive fibers in the second fiber layer, as described below. The adhesive fibers serve to bond fibers together in the laminated nonwoven fabric, improving the strength of the laminated nonwoven fabric and suppressing the elongation of the laminated nonwoven fabric. The adhesive fibers are generally synthetic fibers made of thermoplastic resins and are thermally adhesive fibers that exhibit adhesiveness when heated, but as long as they have adhesiveness, they do not have to be thermally adhesive and may be fibers other than synthetic fibers. The adhesive fibers may be the above-mentioned hydrophilic fibers that have adhesiveness.

[0033] When the adhesive fiber is a synthetic fiber, the synthetic fiber may be made of one or more thermoplastic resins selected from the following: polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polyethylene naphthalate, polylactic acid, polybutylene succinate, and copolymers thereof; polyolefin-based resins such as polypropylene, polyethylene (including high-density polyethylene, low-density polyethylene, linear low-density polyethylene, and the like), polybutene-1, propylene copolymers mainly composed of propylene (including propylene-ethylene copolymers and propylene-butene-1-ethylene copolymers), ethylene-vinyl alcohol copolymers, and ethylene-vinyl acetate copolymers; polyamide-based resins such as nylon 6, nylon 12, and nylon 66; acrylic-based resins; engineering plastics such as polycarbonate, polyacetal, polystyrene, and cyclic polyolefins, and elastomers thereof.

[0034] The synthetic fibers may be single fibers made of a single component (also called "single section") and / or composite fibers made of multiple components (also called "sections"). The composite fibers may be, for example, concentric or eccentric sheath-core composite fibers, islands-in-the-sea composite fibers, side-by-side composite fibers, or splittable composite fibers. The cross section of the fiber may be circular or noncircular, and examples of noncircular shapes include elliptical, Y-shaped, X-shaped, well-shaped, multilobal, polygonal, star-shaped, and the like. The synthetic fibers may also have a hollow cross section. In both the case of single fibers and composite fibers, each section constituting the fiber may be made of one type of resin or a mixture of two or more types of resin.

[0035] When the synthetic fiber is a monofilament, the monofilament may be made of one or more resins selected from the group consisting of the polyolefin resin, the polyester resin, the polyamide resin, and the acrylic resin. More specifically, a monofilament of polyethylene, a monofilament of polypropylene, a monofilament of polyethylene terephthalate, etc. may be used.

[0036] When the synthetic fiber is a composite fiber, two or more components may be arranged so that the thermoplastic resin with the lowest melting point constitutes part of the fiber surface. In this case, when heat is applied under conditions in which the component consisting of the thermoplastic resin with the lowest melting point (hereinafter referred to as the "low melting point component") melts or softens in the process of producing a nonwoven fabric, the low melting point component becomes the adhesive component. The combination of resins (first / second) constituting the composite fiber consisting of a first component which is a thermoplastic resin with a higher melting point and a second component which is a thermoplastic resin with a lower melting point is, for example, a combination of a polyester-based resin and a polyolefin-based resin such as polyethylene terephthalate / polyethylene, polyethylene terephthalate / polypropylene, and polyethylene terephthalate / propylene copolymer, a combination of two types of polyolefin-based thermoplastic resins such as polypropylene / polyethylene, and polypropylene / propylene copolymer, and a combination of two types of polyester-based resins with different melting points.

[0037] Alternatively, the combination of the first and second components may be a combination of biodegradable resins, and such a combination can increase the proportion of biodegradable fibers in the laminated nonwoven fabric. Specifically, the adhesive fiber can be made biodegradable by using polylactic acid as the first component and polybutylene succinate as the second component.

[0038] The thermoplastic resins exemplified as components of the single fiber or composite fiber may contain other components as long as they contain 50% by mass or more of the specifically indicated thermoplastic resin. The specifically indicated thermoplastic resin may be contained in an amount of 80% by mass or more, 90% by mass or more, or the components may consist essentially of the specifically indicated thermoplastic resin. The term "substantially" is used here in consideration of the fact that thermoplastic resins usually contain various additives, etc. For example, in the combination of polyethylene terephthalate / polyethylene, "polyethylene" may contain other thermoplastic resins and additives, etc., as long as it contains 50% by mass or more of polyethylene. This also applies to the following examples.

[0039] When the synthetic fiber is a concentric or eccentric core-sheath type composite fiber in which a thermoplastic resin having a higher melting point constitutes the core component as a first component and a thermoplastic resin having a lower melting point constitutes the sheath component as a second component, the core / sheath combination may be, for example, polypropylene / polyethylene, polypropylene / propylene-ethylene copolymer, polypropylene / propylene-butene-1-ethylene copolymer, polyethylene terephthalate / polyethylene, polyethylene terephthalate / polypropylene, polyethylene terephthalate / propylene copolymer, polytrimethylene terephthalate / polyethylene, polybutylene terephthalate / polyethylene, polyethylene terephthalate / copolyester (for example, polyethylene terephthalate copolymerized with isophthalic acid). These resin combinations may also be used in splittable composite fibers.

[0040] In the case of core-sheath type composite fibers, the volume ratio of the core component to the sheath component (core component:sheath component) is preferably 80:20 to 20:80, more preferably 70:30 to 30:70, and even more preferably 60:40 to 40:60.

[0041] In the case of splittable conjugate fibers, the ratio of the two components (first:second) is preferably 80:20 to 20:80 by volume, more preferably 70:30 to 30:70, and even more preferably 60:40 to 40:60. In the case of splittable conjugate fibers, the number of divisions (i.e., the number of sections in the conjugate fiber) may be, for example, 4 or more and 32 or less, particularly 4 or more and 20 or less, and more particularly 6 or more and 10 or less.

[0042] In this embodiment, the adhesive fibers can preferably be core-sheath type composite fibers (concentric or eccentric) in which the combination of the first component / second component is polyethylene terephthalate / copolymer polyester, polypropylene / polyethylene, or polyethylene terephthalate / polyethylene. These fibers are preferably used because they exhibit adhesiveness at relatively low temperatures (110°C or higher and 130°C or lower) and make the texture of the nonwoven fabric soft after bonding.

[0043] The fineness of the adhesive fiber may be, for example, 1.0 dtex or more and 4.0 dtex or less, particularly 1.5 dtex or more and 2.5 dtex or less, more particularly 1.6 dtex or more and 2.4 dtex or less, and even more particularly 1.7 dtex or more and 2.2 dtex or less. If the fineness of the adhesive fiber is too small, the strength of the laminated nonwoven fabric may be low and the laminated nonwoven fabric may be easily stretched, and if the fineness is too large, the touch of the laminated nonwoven fabric may be hard. If the laminated nonwoven fabric is easily stretched, for example, when the laminated nonwoven fabric is used as a face mask, the position of the openings provided at the positions of the eyes and mouth may be shifted.

[0044] In particular, when the adhesive fiber is a splittable conjugate fiber, the splittable conjugate fiber may have a fineness of 1.0 dtex or more and 4.0 dtex or less before splitting, and may give adhesive fibers of 0.1 dtex or more and less than 1.0 dtex after splitting.

[0045] The fiber length of the adhesive fiber is not particularly limited and may be appropriately selected depending on the manufacturing method of the laminated nonwoven fabric. For example, when the second fiber layer is manufactured by preparing a carded web in the manufacturing of the laminated nonwoven fabric, the adhesive fiber may be a short fiber. The fiber length of this short fiber may be, for example, 20 mm or more and 100 mm or less, particularly 28 mm or more and 75 mm or less, and more particularly 30 mm or more and 65 mm or less. Alternatively, when the second fiber layer is manufactured by an air laying method, the fiber length may be, for example, 2 mm or more and 20 mm or less.

[0046] (Other fibers) The laminated nonwoven fabric of the present embodiment may contain fibers other than the above-mentioned water-repellent cellulose fibers, hydrophilic cellulose fibers, hydrophilic fibers, and adhesive fibers. For example, the first fibrous layer may contain hydrophilic fibers other than cellulose fibers as fibers other than the water-repellent cellulose fibers and hydrophilic cellulose fibers.

[0047] Alternatively, the other fibers may be, for example, synthetic fibers that do not function as adhesive fibers. Specifically, when a synthetic fiber that exhibits adhesiveness when heated at T°C is used as the adhesive fiber, a synthetic fiber that has a melting point higher than T°C and does not exhibit adhesiveness when heated at T°C may be included as the other fiber. Therefore, whether a certain synthetic fiber is included as an adhesive fiber or as another fiber is determined by the synthetic fibers that are also included in the nonwoven fabric, and a certain synthetic fiber may be included as an adhesive fiber or as another fiber.

[0048] For example, when a core-sheath type composite fiber made of polyester (core) / polypropylene (sheath) is used together with a core-sheath type composite fiber made of a combination of polypropylene (core) / polyethylene (sheath), polyethylene is included as another fiber because it exhibits thermal adhesiveness at the lowest temperature. On the other hand, when this is used together with a splittable composite fiber made of a combination of polyethylene terephthalate / nylon 6, polypropylene is included as an adhesive fiber because it exhibits thermal adhesiveness at the lowest temperature. The other fibers may be cellulose fibers whose water immersion time is longer than 60 seconds and shorter than 10 minutes when measured by the method described as the method for evaluating the water repellency of water-repellent cellulose fibers.

[0049] The fineness of the other fibers may be, for example, 1.0 dtex or more and 4.0 dtex or less, particularly 1.3 dtex or more and 2.5 dtex or less, and more particularly 1.4 dtex or more and 2.2 dtex or less. If the fineness of the other fibers is too small, it may cause neps in the nonwoven fabric, affecting the feel, and if it is too large, the surface of the nonwoven fabric may become rough, resulting in a poor feel to the touch.

[0050] The fiber length of the other fibers is not particularly limited and may be appropriately selected depending on the manufacturing method of the nonwoven fabric, etc. The relationship between the manufacturing method of the laminated nonwoven fabric (the manufacturing method of the fiber layer) and the fiber length is as described in relation to the water-repellent cellulose fibers and adhesive fibers.

[0051] (Composition of nonwoven fabric) The laminated nonwoven fabric of this embodiment is formed by integrating a first fiber layer and a second fiber layer laminated on the first fiber layer. In this laminated nonwoven fabric, the first fiber layer contains water-repellent cellulose fibers and hydrophilic cellulose fibers, and the second fiber layer contains hydrophilic fibers and does not contain water-repellent cellulose fibers or contains water-repellent cellulose fibers in a proportion of 20 mass% or less, and both fiber layers are integrated by entanglement of the fibers. When this laminated nonwoven fabric is used as a liquid-impregnated skin dressing sheet, the first fiber layer is brought into contact with the skin.

[0052] The first fiber layer includes both water-repellent cellulose fibers and hydrophilic cellulose fibers. The water-repellent cellulose fibers improve the adhesion between the sheet and the skin when the first fiber layer is brought into contact with the skin. The hydrophilic cellulose fibers ensure the entanglement of the fibers and the integrity of the sheet when the fibers are entangled by spraying a high-pressure fluid flow, particularly a high-pressure water flow, as described below. If the first fiber layer is composed only of water-repellent cellulose fibers, the fibers in the first fiber layer and between the first fiber layer and the second fiber layer may not be sufficiently entangled, and the integrity of the sheet may be impaired. On the other hand, if the proportion of hydrophilic cellulose fibers contained in the first fiber layer is too high, the fibers may be too tightly entangled, and the adhesion of the surface of the first fiber layer may be reduced.

[0053] In this embodiment, the first fiber layer may contain 30% to 80% by mass of water-repellent cellulose fibers and 20% to 70% by mass of hydrophilic cellulose fibers based on the total mass of the first fiber layer. The proportion of water-repellent cellulose fibers may be particularly 40% to 60% by mass, more particularly 45% to 55% by mass. The proportion of hydrophilic cellulose fibers may be particularly 40% to 60% by mass, more particularly 45% to 55% by mass. Here, the proportion of fibers contained in the first fiber layer is the proportion of fibers contained in the first fiber layer before being integrated with the second fiber layer. Therefore, even if some of the fibers constituting the second fiber layer are mixed into the first fiber layer due to integration with the second fiber layer, the mixed fibers are not included in the first fiber layer.

[0054] Alternatively, in the laminated nonwoven fabric of this embodiment, the first fiber layer may contain water-repellent cellulose fibers and hydrophilic cellulose fibers so that the spot absorbency on the surface of the first fiber layer of the laminated nonwoven fabric is 35% or more when measured according to the following method. The spot absorbency on the surface of the first fiber layer may be particularly 50% or more, more particularly 60% or more, and even more particularly 70% or more. The upper limit of the spot absorbency may be, for example, 100%. The lower the spot absorbency on the surface of the first fiber layer, the higher the water repellency, and when the first fiber layer is used as a skin-contacting surface in a liquid-impregnated skin application sheet, the better the adhesion to the skin tends to be. On the other hand, if the spot absorbency is too low, the proportion of water-repellent cellulose fibers is large, and when the fibers are entangled with each other by a high-pressure fluid flow (particularly a water flow) as described below, the fibers may not be sufficiently entangled with each other, and the integrity of the sheet may be impaired.

[0055] (Spot absorption rate) (1) Prepare a nonwoven fabric (22 cm or more vertically and 10 cm or more horizontally) and place it so that the surface to be measured (if the surface of the first fiber layer is the surface to be measured, then the surface of the first fiber layer) is on top. Place a polyethylene sheet under the nonwoven fabric to prevent the distilled water from being absorbed by anything other than the nonwoven fabric. (2) Put distilled water into a dropper and drip one drop (0.049 mL) onto the nonwoven fabric at a distance of 1 cm from the fabric, at least 2 cm away from the edge of the fabric. (3) Place one drop of distilled water 2 cm away from the location where the distilled water was placed, and repeat the process to place distilled water in a total of 40 locations. (4) Distilled water is dropped onto 40 spots, and after 10 minutes, the number of spots P (0≦P≦40) where droplets of liquid no longer exist on the surface of the nonwoven fabric is counted, and the spot absorbency (%) is calculated using the following formula. Spot absorption rate (%) = P x 100 / 40

[0056] The spot absorbency tends to be large even when the proportion of hydrophilic fibers is small, and the first fiber layer of the nonwoven fabric of this embodiment has a relatively large spot absorbency, close to 100% or 100%, even though it contains water-repellent cellulose fibers. Therefore, it may be difficult to adjust the proportion of hydrophilic cellulose fibers only by the spot absorbency. In the laminated nonwoven fabric of this embodiment, the first fiber layer may contain water-repellent cellulose fibers and hydrophilic cellulose fibers so that the spot absorption time on the surface of the first fiber layer of the laminated nonwoven fabric is 0.6 seconds or more when measured according to the following method. The spot absorption time on the surface of the first fiber layer may be particularly 1.2 seconds or more, more particularly 1.6 seconds or more, and even more particularly 2.5 seconds or more. When the spot absorption time on the surface of the first fiber layer is a predetermined time or more, the surface of the first fiber layer exhibits good water repellency, and when the first fiber layer is used as a skin-contact surface in a liquid-impregnated skin application sheet, the surface tends to have good adhesion to the skin.

[0057] (Spot absorption time) (1) Prepare a nonwoven fabric (22 cm or more vertically and 10 cm or more horizontally) and place it so that the surface to be measured (if the surface of the first fiber layer is the surface to be measured, then the surface of the first fiber layer) is on top. Place a polyethylene sheet under the nonwoven fabric to prevent the distilled water from being absorbed by anything other than the nonwoven fabric. (2) Put distilled water into a dropper and drip one drop (0.049 mL) onto the nonwoven fabric at a distance of 1 cm from the fabric, at least 2 cm away from the edge of the fabric. (3) After distilled water is dropped onto the nonwoven fabric, the time (absorption time) until the droplets of liquid no longer remain on the nonwoven fabric surface is measured. (4) One drop of distilled water is dropped 2 cm away from the location where the distilled water was dropped, and the absorption time is measured. Distilled water is dropped at a total of 40 locations. (5) The average absorption time for the 40 spots is calculated as the spot absorption time (seconds). If there are five or more spots on the nonwoven fabric where liquid remains after 10 minutes, the spot absorption time for the surface of the first fiber layer of that nonwoven fabric is considered to be 600 seconds.

[0058] The spot absorption time tends to be long even when the proportion of water-repellent cellulose fibers is small, and the first fiber layer of the nonwoven fabric of this embodiment may have a spot absorption time close to or at the upper limit (600 seconds) even though it contains hydrophilic cellulose fibers. Therefore, it may not be possible to distinguish between a fiber layer containing water-repellent cellulose fibers and hydrophilic cellulose fibers and a fiber layer containing only water-repellent cellulose fibers by the spot absorption time alone. Therefore, in this embodiment, it is preferable to adjust the proportions of the two cellulose fibers using two parameters, the spot absorption rate and the spot absorption time. Using these two parameters makes it easy to adjust the proportion of fibers in the fiber layer.

[0059] Alternatively, in the laminated nonwoven fabric of this embodiment, the first fiber layer may contain water-repellent cellulose fibers and hydrophilic cellulose fibers so that the contact angle with water on the surface of the first fiber layer of the laminated nonwoven fabric after 10 minutes is 90 degrees or less when the contact angle is measured according to the following method. The contact angle on the surface of the first fiber layer after 10 minutes may be particularly 80 degrees or less, more particularly 70 degrees or less, and even more particularly 60 degrees or less. The lower limit of the contact angle may be, for example, 0 degrees. The larger the contact angle on the surface of the first fiber layer after 10 minutes, the higher the water repellency, and when the first fiber layer is used as a skin-contacting surface in a liquid-impregnated skin-applied sheet, the better the adhesion to the skin tends to be. On the other hand, if the contact angle after 10 minutes is too large, the proportion of water-repellent cellulose fibers is high, and when the fibers are entangled with each other by a high-pressure fluid flow (particularly a water flow) as described below, the fibers may not be sufficiently entangled, and the integrity of the sheet may be impaired.

[0060] (Method for measuring the contact angle of nonwoven fabric with water) (1) Prepare a nonwoven fabric (22 cm or more vertically and 10 cm or more horizontally) and place it so that the surface to be measured (if the surface of the first fiber layer is the surface to be measured, then the surface of the first fiber layer) is on top. Place a polyethylene sheet under the nonwoven fabric to prevent the ion-exchanged water from being absorbed by anything other than the nonwoven fabric. (2) Pour ion-exchanged water into a 25 mL burette (manufactured by AS ONE) and place it on the burette stand. do. (3) Set the burette so that the distance between the tip and the nonwoven fabric is 1 cm. (4) One drop (0.049 mL) of ion-exchanged water is dropped, and 10 minutes after the water hits the surface, the contact angle α of the nonwoven fabric 10 with the water droplet 20 is measured as shown in Figure 1. Measurements are performed at three locations, and the contact angles on both the left and right sides of the water droplet are measured, for a total of six angles, which are then averaged. If the water droplet is absorbed into the nonwoven fabric within 10 minutes, the measurement is repeated at another location on the nonwoven fabric. However, if there are fewer than three measurement locations even after 40 measurements are performed (i.e., there are fewer than three locations where water droplets remain 10 minutes after the ion-exchanged water is dropped), the contact angle is considered to be 0 degrees.

[0061] In this embodiment, when the first fiber layer and the second fiber layer are integrated by entanglement of the fibers, it may be difficult to determine the ratio of fibers contained in each fiber layer before integration because the fibers of each fiber layer may move to the other fiber layer, etc. In such a case, the measurement of the spot absorption time, spot absorption rate, and contact angle can be indicators for knowing whether the surface of the first fiber layer has appropriate water repellency due to the water-repellent cellulose fibers.

[0062] In this embodiment, the first fiber layer may contain adhesive fibers and / or other fibers in addition to the water-repellent cellulose fibers and hydrophilic cellulose fibers. When the first fiber layer contains fibers other than the water-repellent cellulose fibers and hydrophilic cellulose fibers, the proportion of the fibers may be, for example, 40 mass% or less, particularly 30 mass% or less, more particularly 20 mass% or less, based on the total mass of the first fiber layer. If the proportion of fibers other than the water-repellent cellulose fibers and hydrophilic cellulose fibers is too high, the proportion of the water-repellent cellulose fibers and / or hydrophilic cellulose fibers will be small, which may reduce the adhesion of the sheet to the skin or may cause insufficient entanglement of the fibers. The first fiber layer may be composed of only the water-repellent cellulose fibers and hydrophilic cellulose fibers.

[0063] The second fiber layer contains hydrophilic fibers and does not contain water-repellent cellulose fibers, or if it does contain them, the proportion is 20% by mass or less. It is preferable that the second fiber layer does not contain water-repellent cellulose fibers. The second fiber layer plays a role in ensuring the mechanical strength of the laminated nonwoven fabric. As described below, when fibers are entangled by spraying a high-pressure fluid flow, particularly a high-pressure water flow, the inclusion of hydrophilic fibers in the second fiber layer makes the entanglement of the fibers stronger, and the mechanical strength of the nonwoven fabric can be increased. On the other hand, since water-repellent cellulose fibers have a particularly low affinity for water, they tend not to contribute to the entanglement of the fibers. Therefore, in this embodiment, it is preferable that the second fiber layer does not contain water-repellent cellulose fibers, and even if they are contained, the proportion is 20% by mass or less.

[0064] Furthermore, the second fiber layer contains a large amount of hydrophilic fibers, which allows the second fiber layer to retain a large amount of liquid. In particular, when the hydrophilic fibers are hydrophilic cellulose fibers, the fibers have high liquid absorption properties, and therefore, when the second fiber layer contains a large amount of these fibers, the second fiber layer can retain an even larger amount of liquid.

[0065] In this embodiment, the second fiber layer may contain hydrophilic fibers in an amount of 50% by mass or more based on the total mass of the second fiber layer. The ratio of hydrophilic fibers may be particularly 60% by mass or more, more particularly 70% by mass or more, and even more particularly 80% by mass or more. The upper limit of the ratio of hydrophilic fibers may be, for example, 100% by mass, particularly 95% by mass, and more particularly 90% by mass. Here, the ratio of fibers contained in the second fiber layer is the ratio of fibers contained in the second fiber layer before being integrated with the first fiber layer. Therefore, even if some of the fibers constituting the first fiber layer are mixed into the second fiber layer due to integration with the first fiber layer, the mixed fibers are not included in the second fiber layer.

[0066] Alternatively, in the laminated nonwoven fabric of this embodiment, the second fiber layer may contain hydrophilic fibers so that the spot absorbency on the surface of the second fiber layer of the laminated nonwoven fabric is 97% or more. The spot absorbency on the surface of the second fiber layer may particularly be 99% or more, more particularly 100%. The spot absorbency on the surface of the second fiber layer can be measured by placing the nonwoven fabric so that the second fiber layer is on top.

[0067] Alternatively, in the laminated nonwoven fabric of this embodiment, the second fiber layer may contain hydrophilic fibers such that the spot absorption time measured on the surface of the second fiber layer of the laminated nonwoven fabric is 0.1 seconds or less. The spot absorption time on the surface of the second fiber layer may particularly be 0 seconds. The spot absorption time on the surface of the second fiber layer can be measured by placing the nonwoven fabric so that the second fiber layer is on top.

[0068] Alternatively, in the laminated nonwoven fabric of this embodiment, the second fiber layer may contain hydrophilic fibers such that, when the contact angle with water on the surface of the second fiber layer of the laminated nonwoven fabric is measured according to the above-mentioned method, the contact angle with water on the surface of the second fiber layer may particularly be 0 degree. The contact angle with water on the surface of the second fiber layer can be measured by placing the nonwoven fabric so that the second fiber layer is on top.

[0069] The second fiber layer may contain adhesive fibers in addition to the hydrophilic fibers. In this case, it is preferable that the fibers in the laminated nonwoven fabric are bonded to each other by the adhesive fibers. The adhesive fibers bond the fibers to each other, which can further improve the mechanical strength of the laminated nonwoven fabric. In addition, when the adhesive fibers are contained in the second fiber layer and are preferably not contained in the first fiber layer, the effect on the touch can be reduced and the mechanical strength of the nonwoven fabric can be improved.

[0070] When the second fiber layer contains adhesive fibers, the adhesive fibers may be contained in an amount of, for example, 10% by mass to 30% by mass, particularly 15% by mass to 28% by mass, and more particularly 20% by mass to 25% by mass, based on the total mass of the second fiber layer. If the proportion of the adhesive fibers is too high, the liquid retention of the second fiber layer, and therefore the liquid retention of the entire laminated nonwoven fabric, may decrease.

[0071] When the adhesive fiber is a splittable conjugate fiber, the splittable conjugate fiber before splitting may be contained in an amount of 10% by mass to 30% by mass, particularly 15% by mass to 28% by mass, more particularly 20% by mass to 25% by mass, based on the total mass of the second fiber layer. After splitting, the fiber exhibiting adhesiveness may be contained in an amount of 5% by mass to 15% by mass, particularly 7.5% by mass to 14% by mass, more particularly 10% by mass to 12.5% ​​by mass, based on the total mass of the second fiber layer.

[0072] In this embodiment, the second fiber layer may contain other fibers in addition to the hydrophilic fibers and adhesive fibers. When the second fiber layer contains other fibers, the proportion of the other fibers may be, for example, 40% by mass or less, particularly 30% by mass or less, more particularly 25% by mass or less, based on the total mass of the second fiber layer. If the proportion of the other fibers is too large, the proportion of the hydrophilic cellulose fibers and, if included, the adhesive fibers will be small, and the liquid retention and / or mechanical strength of the laminated nonwoven fabric may be insufficient. The second fiber layer may be composed of only hydrophilic fibers, or only hydrophilic fibers and adhesive fibers.

[0073] In the laminated nonwoven fabric of this embodiment, when the second fiber layer contains hydrophilic cellulose fibers as hydrophilic fibers, the layer may contain, for example, 85% by mass or more, particularly 90% by mass or more, and more particularly 95% by mass or more of cellulose fibers (including both water-repellent cellulose fibers and hydrophilic cellulose fibers, and also including cellulose fibers that do not fall into either category) based on the total mass of the laminated nonwoven fabric. By containing more cellulose fibers, the biodegradability of the laminated nonwoven fabric becomes higher, and a sheet using the laminated nonwoven fabric can be provided as a product with low environmental impact. The laminated nonwoven fabric of this embodiment may be composed of cellulose fibers only.

[0074] In this embodiment, the first fiber layer and the second fiber layer are integrated by entangling the fibers. The entanglement of the fibers may be achieved, for example, by needle punching or high-pressure fluid flow (particularly water flow) entanglement. In this embodiment, it is preferable that the fibers are integrated by high-pressure fluid flow (particularly water flow) entanglement. The high-pressure fluid flow entanglement can tightly entangle the fibers to make the surface of the nonwoven fabric smooth. In addition, when the high-pressure fluid flow is a high-pressure water flow, the entanglement of the hydrophilic cellulose fibers and hydrophilic fibers contained in the first fiber layer and the second fiber layer is more likely to be stronger.

[0075] In the laminated nonwoven fabric of the present embodiment, when the second fiber layer contains adhesive fibers, the fibers may be bonded to each other by the adhesive fibers. By bonding the fibers to each other in addition to entangling them, the mechanical strength of the nonwoven fabric can be further improved.

[0076] The laminated nonwoven fabric of this embodiment may be a two-layer structure consisting of a first fiber layer and a second fiber layer, or a three-layer structure in which the first fiber layer is disposed on both surfaces of the second fiber layer. The two-layer laminated nonwoven fabric can reduce the basis weight of the laminated nonwoven fabric, making the laminated nonwoven fabric easier to bend. The ease of bending leads to the ability to follow unevenness and improves adhesion. In a nonwoven fabric having a two-layer structure consisting of a first fiber layer and a second fiber layer, for example, a part of the constituent fibers of the first fiber layer may be colored, or a mark may be printed on one of the surfaces after the laminated nonwoven fabric is produced, so that it is clear which surface the first fiber layer, which is the skin contact surface, is located on.

[0077] In this embodiment, the basis weight of each fiber layer is not particularly limited. The basis weight of the first fiber layer is, for example, 10 g / m 2 Above 15g / m 2 or more, more particularly 20 g / m 2 The upper limit of the basis weight of the first fiber layer is, for example, 70 g / m 2 Especially, 50 g / m 2 , more particularly 30 g / m 2 The basis weight of the second fiber layer is, for example, 10 g / m 2 or more, in particular 15 g / m 2 More particularly, 20 g / m 2 The upper limit of the basis weight of the second fiber layer is, for example, 70 g / m 2 Especially, 50 g / m 2 , more particularly 30 g / m 2 The ratio of the basis weight of the first fiber layer to the second fiber layer (first / second) may be, for example, 7 / 1 to 1 / 7, particularly 3 / 1 to 1 / 3, and more particularly 1.5 / 1 to 1 / 1.5. When the ratio of the basis weight of the two fiber layers is within these ranges, a nonwoven fabric that shows good adhesion and is practical in terms of liquid retention and mechanical strength tends to be obtained.

[0078] The basis weight of the entire laminated nonwoven fabric is not particularly limited, and may be, for example, 30 g / m 2 or more, in particular 40 g / m 2 More particularly, 45 g / m 2The upper limit of the basis weight of the entire laminated nonwoven fabric is, for example, 80 g / m 2 and in particular 70 g / m 2 , more particularly 60 g / m 2 The basis weight of the nonwoven fabric is determined depending on the application, the amount of liquid to be impregnated, etc. For example, when the sheet is a face mask, the basis weight of the nonwoven fabric may be 30 g / m 2 More than 80g / m 2 Below, especially 40g / m 2 More than 60g / m 2 If the sheet is an eye sheet (also called an eye pack), the basis weight of the nonwoven fabric is 40 g / m 2 More than 80g / m 2 Below, especially 45g / m 2 More than 70g / m 2 The following may be used.

[0079] The thickness of the laminated nonwoven fabric may be, for example, 0.2 mm or more, particularly 0.3 mm or more, more particularly 0.4 mm or more, when a load of 294 Pa is applied when dry. The thickness of the nonwoven fabric may be, for example, 1.3 mm or less, particularly 1.2 mm or less, more particularly 1.0 mm or less. The thickness of the entire nonwoven fabric may be, for example, 0.3 mm or more, particularly 0.4 mm or more, more particularly 0.5 mm or more, when a load of 1.96 kPa is applied when dry. The thickness of the nonwoven fabric when the load is applied may be, for example, 0.9 mm or less, particularly 0.8 mm or less, more particularly 0.7 mm or less. If the thickness of the laminated nonwoven fabric is too small, the amount of liquid that can be impregnated into the nonwoven fabric may be reduced, and a predetermined amount of liquid may not be supplied to the skin. If the thickness of the entire laminated nonwoven fabric is too large, it may be difficult to make the sheet conform to the curved surface of the skin, and the sheet may partially float, making it difficult to evenly cover the skin with the entire sheet.

[0080] The laminated nonwoven fabric of this embodiment may have a water retention rate of, for example, 1200% or less when the water retention rate is measured by the method described in the examples below. The water retention rate of the nonwoven fabric of this embodiment may be, in particular, 1100% or less, more particularly, 1000% or less, and even more particularly, 930% or less. The lower limit of the water retention rate of this embodiment may be, for example, 700%, in particular, 750%, and more particularly, 800%. Since the nonwoven fabric of this embodiment contains water-repellent cellulose fibers, it tends not to have a high water retention rate. A laminated nonwoven fabric with a water retention rate that is not excessively large can reduce the amount of liquid remaining in the sheet to be discarded after covering the skin and treating the skin with liquid, thereby reducing the loss of liquid.

[0081] The water retention rate may vary depending on the type and ratio of the fibers constituting each fiber layer and the basis weight of the laminated nonwoven fabric. Therefore, in the laminated nonwoven fabric of the present embodiment, these may be adjusted so as to obtain the above water retention rate.

[0082] The laminated nonwoven fabric of this embodiment may have a tensile strength in the MD direction when dry of, for example, 30 N / 5 cm or more and 160 N / 5 cm or less, particularly 34 N / 5 cm or more and 150 N / 5 cm or less, and more particularly 38 N / 5 cm or more and 140 N / 5 cm or less. If the tensile strength in the MD direction when dry is too low, the fabric may break during product processing. If the tensile strength in the MD direction when dry is too high, the texture of the nonwoven fabric may not be good.

[0083] The laminated nonwoven fabric of this embodiment may have a tensile strength in the CD direction when dry of, for example, 4.5 N / 5 cm or more and 30 N / 5 cm or less, particularly 4.9 N / 5 cm or more and 25 N / 5 cm or less, and more particularly 5.3 N / 5 cm or more and 23 N / 5 cm or less. If the tensile strength in the CD direction when dry is too low, vertical streaks are likely to form in the nonwoven fabric. If the tensile strength in the CD direction when dry is too high, the texture of the nonwoven fabric may not be good.

[0084] The laminated nonwoven fabric of this embodiment may have an elongation percentage in the MD direction when dry of, for example, 10% to 60%, particularly 15% to 55%, and more particularly 18% to 50%. The laminated nonwoven fabric of this embodiment may have an elongation percentage in the CD direction when dry of, for example, 60% to 160%, particularly 70% to 150%, and more particularly 80% to 140%. If the elongation percentage in the MD or CD direction when dry is too low, the texture of the nonwoven fabric may not be good. If the elongation percentage in the MD or CD direction when dry is too high, defects are likely to occur during punching during product processing.

[0085] The laminated nonwoven fabric of this embodiment may have a stress at 10% elongation in the MD direction when dry of, for example, 2.0 N / 5 cm or more and 110 N / 5 cm or less, particularly 3.0 N / 5 cm or more and 100 N / 5 cm or less, more particularly 4.0 N / 5 cm or more and 95 N / 5 cm or less. The laminated nonwoven fabric of this embodiment may have a stress at 10% elongation in the CD direction when dry of, for example, 0.3 N / 5 cm or more and 4.0 N / 5 cm or less, particularly 0.4 N / 5 cm or more and 3.0 N / 5 cm or less, more particularly 0.5 N / 5 cm or more and 2.7 N / 5 cm or less. If the stress at 10% elongation in the MD direction or CD direction when dry is too low, defects are likely to occur during punching during product processing. If the stress at 10% elongation in the MD direction or CD direction when dry is too high, the texture of the nonwoven fabric may not be good.

[0086] The laminated nonwoven fabric of this embodiment may have a tensile strength in the MD direction when wet of, for example, 50 N / 5 cm or more and 150 N / 5 cm or less, particularly 53 N / 5 cm or more and 140 N / 5 cm or less, more particularly 55 N / 5 cm or more and 130 N / 5 cm or less. The laminated nonwoven fabric of this embodiment may have a tensile strength in the CD direction when wet of, for example, 8.0 N / 5 cm or more and 35 N / 5 cm or less, particularly 9.0 N / 5 cm or more and 32 N / 5 cm or less, more particularly 10 N / 5 cm or more and 25 N / 5 cm or less. If the tensile strength in the MD direction or CD direction when wet is too low, the liquid-impregnated skin application sheet that has been produced as a product may break when removed. If the tensile strength in the MD direction or CD direction when wet is too high, the laminated nonwoven fabric may be difficult to bend, and its ability to conform to uneven skin may decrease.

[0087] The laminated nonwoven fabric of the present embodiment may have an extensibility in the MD direction when wet of, for example, 15% to 65%, particularly 20% to 60%, and more particularly 25% to 55%. The laminated nonwoven fabric of the present embodiment may have an extensibility in the CD direction when wet of, for example, 80% to 160%, particularly 90% to 150%, and more particularly 95% to 142%. If the extensibility in the MD or CD direction when wet is too low, it becomes difficult to attach the laminated nonwoven fabric to the skin. If the extensibility in the MD or CD direction when wet is too high, the finished liquid-impregnated skin application sheet may be significantly stretched when removed.

[0088] The laminated nonwoven fabric of this embodiment may have a stress at 10% elongation in the MD direction when wet of, for example, 2.0 N / 5 cm or more and 80 N / 5 cm or less, particularly 2.5 N / 5 cm or more and 70 N / 5 cm or less, more particularly 3.0 N / 5 cm or more and 63 N / 5 cm or less. The laminated nonwoven fabric of this embodiment may have a stress at 10% elongation in the CD direction when wet of, for example, 0.30 N / 5 cm or more and 1.5 N / 5 cm or less, particularly 0.35 N / 5 cm or more and 1.2 N / 5 cm or less, more particularly 0.40 N / 5 cm or more and 1.1 N / 5 cm or less. If the stress at 10% elongation in the MD or CD direction when wet is too low, it becomes difficult to attach the laminated nonwoven fabric to the skin. If the stress at 10% elongation in the MD or CD when wet is too high, when the liquid-impregnated skin covering sheet has eyes, a mouth, etc. punched out, the position of the eyes, mouth, etc. may stretch and shift when applied, making it difficult to use.

[0089] In the laminated nonwoven fabric of this embodiment, the coefficient of variation of the dynamic friction coefficient of the first fiber layer surface may be, for example, 0.010 to 0.050, particularly 0.015 to 0.040, and more particularly 0.020 to 0.030. If the coefficient of variation of the dynamic friction coefficient of the first fiber layer surface is too high, the texture of the laminated nonwoven fabric may not be good. If the coefficient of variation of the dynamic friction coefficient of the first fiber layer surface is too low, it may be difficult for the laminated nonwoven fabric to conform to the unevenness of the skin.

[0090] In the laminated nonwoven fabric of this embodiment, the coefficient of variation of the dynamic friction coefficient of the second fiber layer surface may be, for example, 0.010 to 0.070, particularly 0.020 to 0.060, and more particularly 0.026 to 0.050. If the coefficient of variation of the dynamic friction coefficient of the second fiber layer surface is too high, the texture of the laminated nonwoven fabric may not be good. If the coefficient of variation of the dynamic friction coefficient of the second fiber layer surface is too low, the density of the second fiber layer is likely to be high, and the water retention may be reduced.

[0091] In the laminated nonwoven fabric of this embodiment, the adhesion strength of the surface of the first fiber layer after 15 minutes is, for example, 20 mN / cm 2 More than 65mN / cm 2It may be equal to or less than 35 mN / cm 2 More than 60mN / cm 2 or less, more particularly 40 mN / cm 2 More than 55mN / cm 2 If the adhesion strength of the first fiber layer surface after 15 minutes is too high, the laminated nonwoven fabric will be difficult to peel off from the skin. If the adhesion strength of the first fiber layer surface after 15 minutes is too low, the laminated nonwoven fabric will easily slip off from the skin.

[0092] (Nonwoven fabric manufacturing method) The laminated nonwoven fabric of the present embodiment is, for example, Producing a first fibrous web comprising water repellent cellulosic fibers and hydrophilic cellulosic fibers; preparing a second fibrous web containing hydrophilic fibers and no water-repellent cellulosic fibers, or containing water-repellent cellulosic fibers in an amount of 20% by mass or less; overlapping the first fiber web and the second fiber web to produce a laminated fiber web; Subjecting the laminated fiber web to a process for entangling the fibers. The composition can be produced by a production method including the steps of:

[0093] The first fiber web is a web that will become the first fiber layer, and the second fiber web is a web that will become the second fiber layer. The types and ratios of fibers contained in the first fiber web and the second fiber web are as described above in relation to the first fiber layer and the second fiber layer, so they will not be described here. The basis weights of the first fiber web and the second fiber web are as described above in relation to the first fiber layer and the second fiber layer, so they will not be described here. The lamination form of the first fiber web and the second fiber web is also as described above as the lamination form of the first fiber layer and the second fiber layer, so they will not be described here.

[0094] The first and second fiber webs can be prepared by a known method. The form of each fiber web may be any one selected from, for example, a parallel web, a cross web, a card web such as a semi-random web or a random web, an air-laid web, and a wet-laid paper web. The forms of the first and second fiber webs may be different from each other.

[0095] The first fiber web and the second fiber web are superimposed to form a laminated fiber web. The laminated fiber web is subjected to a treatment for entangling the fibers. The treatment for entangling the fibers may be, for example, an entangling treatment using a high-pressure fluid flow.

[0096] In the high-pressure fluid flow treatment, the high-pressure fluid is, for example, a high-pressure gas such as compressed air, or a high-pressure liquid such as high-pressure water. In the manufacture of nonwoven fabrics, a hydroentanglement treatment using high-pressure water as the high-pressure fluid is often used, and in the present embodiment, the hydroentanglement treatment is preferably used from the viewpoint of ease of implementation. In the following, a manufacturing method in which high-pressure water (hereinafter also simply referred to as "water flow") is used as the high-pressure fluid will be described.

[0097] The hydroentanglement treatment is carried out by placing the laminated fiber web on a support and spraying a columnar water stream. For example, the support is preferably a plain weave support of 80 mesh or more and 100 mesh or less. The hydroentanglement treatment may be carried out by spraying a water stream with a water pressure of 1 MPa or more and 15 MPa or less on the front and back surfaces of the laminated fiber web 1 to 5 times each from a nozzle having orifices with a hole diameter of 0.05 mm or more and 0.5 mm or less, spaced 0.3 mm or more and 1.5 mm or less. The water pressure is preferably 1 MPa or more and 10 MPa or less, more preferably 1 MPa or more and 7 MPa or less.

[0098] When the laminated fiber web is a two-layered web consisting of a first fiber web and a second fiber web, it is preferable to spray the water stream onto the second fiber web first and then onto the first fiber web. By first exposing the second fiber web to the water stream, entanglement by the hydrophilic fibers contained in the second fiber web progresses to a certain degree. Therefore, even if the water-repellent cellulose fibers repel water when the water stream is subsequently sprayed onto the first fiber web, entanglement by the water stream tends to progress smoothly.

[0099] When the second fiber web contains adhesive fibers, the laminated fiber webs may be subjected to a bonding treatment so that the fibers are bonded together in the resulting laminated nonwoven fabric. The bonding treatment may be a thermal bonding treatment, or bonding by electron beam irradiation or ultrasonic welding. By the heat treatment, the adhesive fibers (e.g., the low melting point components of the composite fibers) melt or soften by heat during the heat treatment, and the fibers constituting the laminated fiber webs can be bonded together.

[0100] The heat treatment may be, for example, a hot air processing treatment in which hot air is blown, a heat roll processing (heat embossing roll processing), or a heat treatment using infrared rays. The hot air processing treatment may be carried out using a device that blows hot air at a predetermined temperature onto the laminated fiber web, for example, a hot air penetration type heat treatment machine or a hot air blowing type heat treatment machine.

[0101] The heat treatment temperature (for example, the temperature of hot air) may be a temperature at which a component constituting the adhesive fiber and functioning as an adhesive component softens or melts. For example, the heat treatment temperature may be a temperature equal to or higher than the melting point of the component. For example, when the adhesive fiber contains polyethylene as a component and polyethylene is used as an adhesive component, the heat treatment temperature may be 130°C to 150°C, and when polybutylene succinate is used as an adhesive component, the heat treatment temperature may be 120°C to 133°C.

[0102] (Liquid-impregnated skin covering sheet) By impregnating the laminated nonwoven fabric of this embodiment with a liquid, a liquid-impregnated skin covering sheet for covering the skin of a human or animal can be obtained. The liquid to be impregnated and the amount of impregnation are appropriately selected depending on the application. When the sheet is provided as a liquid-impregnated skin covering sheet for humans, such as a face mask for humans, a keratin care sheet, and a décolleté sheet, the liquid (e.g., a cosmetic) containing an active ingredient may be impregnated in an amount of 500 parts by mass or more and 2000 parts by mass or less, particularly 600 parts by mass or more and 1800 parts by mass or less, and more particularly 700 parts by mass or more and 1500 parts by mass or less, per 100 parts by mass of the nonwoven fabric. Examples of the active ingredient include, but are not limited to, moisturizing ingredients, keratin softening ingredients, antiperspirant ingredients, fragrance ingredients, whitening ingredients, blood circulation promoting ingredients, UV protection ingredients, and slimming ingredients.

[0103] The face mask is provided in a shape suitable for covering the face, and further in a form in which, for example, openings or cutouts are provided by punching as necessary in areas corresponding to the eyes, nose, and mouth. Alternatively, the face mask may be shaped to cover only a part of the face (e.g., the eyes, mouth, nose, or cheeks). Alternatively, the face mask may be provided as a set consisting of a sheet covering the area around the eyes and a sheet covering the area around the mouth, or as a set of sheets separately covering three or more areas.

[0104] The keratin care sheet is a skin covering sheet used on the heels, elbows, knees, etc., where the keratin is thick and easily hardened, and is impregnated with a liquid containing a keratin softening component and a moisturizing component, etc., to promote moisturizing and softening of the keratin, or to promote the removal of excess keratin. The nonwoven fabric of this embodiment can be used as a substrate in a keratin care sheet that exhibits either of these effects and efficacy. A keratin care sheet, for example a keratin care sheet for the heel, is provided in a form having cuts and / or notches and / or openings punched out of a portion of the sheet so that the sheet can easily fit the curve of the heel when applied.

[0105] The liquid-impregnated skin covering sheet may be a moisturizing sheet impregnated with a liquid containing a moisturizing component or other active ingredient, which is used to moisturize or otherwise care for any part of the body (e.g., the neck, the back of the hand, or the area from the neck to the chest (also called the décolleté)). Alternatively, the liquid-impregnated skin covering sheet may be a slimming sheet impregnated with a liquid containing a slimming component. The slimming sheet is used by being attached to, for example, the thighs or abdomen.

[0106] The liquid-impregnated skin-applying sheet using the laminated nonwoven fabric of this embodiment exhibits good adhesion when the first fiber layer of the laminated nonwoven fabric is used in contact with the skin. The reason why the surface of the first fiber layer adheres well to the skin is presumably because, when the first fiber layer and the second fiber layer are integrated by a high-pressure fluid flow (particularly a water flow), the water-repellent cellulose fibers in the first fiber layer repel the fluid, so that entanglement does not progress easily, and the degree of freedom is relatively high. However, this presumption does not limit the scope of the present invention. In addition, since most of the fibers constituting the surface that contacts the skin of the laminated nonwoven fabric of this embodiment are cellulose fibers, it is unlikely to give an itchy feel and gives a good feel. EXAMPLES

[0107] The present embodiment will now be described with reference to examples. The following fibers were prepared for use in this example. Water-repellent cellulose fiber 1: Viscose rayon with a fineness of 1.7 dtex and a fiber length of 40 mm, the fiber surface of which was treated with a hydrocarbon-based water repellent (product name: Ecorepellent, manufactured by Daiwabo Rayon Co., Ltd.). When the water repellency of this fiber was evaluated by the above method, the sample did not sink even after 10 minutes had passed, and almost the entire sample floated on the water surface. Hydrophilic cellulose fiber A: Viscose rayon with a fineness of 1.7 dtex and a fiber length of 40 mm (product name: Corona CD, manufactured by Daiwabo Rayon Co., Ltd.). When the water repellency (hydrophilicity) of this fiber was evaluated by the above-mentioned method, after the sample was placed on the water surface, it reached the bottom of the beaker within 30 seconds. Hydrophilic cellulose fiber B: Solvent-spun cellulose fiber with a fineness of 1.7 dtex and a fiber length of 38 mm (product name: Lyocell, manufactured by Lenzing). When the water repellency (hydrophilicity) of this fiber was evaluated by the above-mentioned method, after the sample was placed on the water surface, it reached the bottom of the beaker within 30 seconds. Adhesive fiber A: a concentric core-sheath type composite fiber (product name: NBF(H), manufactured by Daiwabo Polytech Co., Ltd.) with a fineness of 1.7 dtex, fiber length of 51 mm, a core of polypropylene, and a sheath of high-density polyethylene (melting point: approximately 133°C). When the water repellency (hydrophilicity) of this fiber was evaluated by the above method, after the sample was placed on the water surface, it did not reach the bottom of the beaker within 60 seconds. Adhesive fiber B: A concentric core-sheath type composite fiber (product name: NBF(KK)PL, manufactured by Daiwabo Polytech Co., Ltd.) with a fineness of 2.2 dtex, fiber length of 45 mm, a core of polylactic acid, and a sheath of polybutylene succinate (melting point: approximately 115°C). When the water repellency (hydrophilicity) of this fiber was evaluated by the above method, after the sample was placed on the water surface, it did not reach the bottom of the beaker within 60 seconds. Adhesive fiber C: A splittable composite fiber (product name: DFS (SH), manufactured by Daiwabo Polytech Co., Ltd.) with a fineness of 2.2 dtex, fiber length of 45 mm, and polyethylene terephthalate and high density polyethylene (melting point: approximately 133°C) arranged alternately in a chrysanthemum shape, with the number of divisions being 8. When the water repellency (hydrophilicity) of this fiber was evaluated by the above method, after the sample was placed on the water surface, it did not reach the bottom of the beaker within 60 seconds.

[0108] Example 1 [First fiber layer] Water-repellent cellulose fiber 1 (50% by mass) and hydrophilic cellulose fiber A (50% by mass) were mixed and carded into a cardboard sheet with a target weight of approximately 25 g / m using a parallel carding machine. 2 A first fibrous web was prepared. [Second fiber layer] A mixture of 80% by mass of hydrophilic cellulose fiber A and 20% by mass of adhesive fiber A was carded into a cardboard with a target weight of approximately 25 g / m using a parallel carding machine. 2 A second fibrous web was prepared by [Laminated nonwoven fabric] A second fiber web was laminated on the first fiber web to form a laminated fiber web, and the laminated fiber web was placed on a 90-mesh plain weave support and transported at a speed of 4 m / min, while a water stream of 1.5 MPa was sprayed once on the surface of the second fiber web, and then a water stream of 1.5 MPa was sprayed once on the surface of the first fiber web, for hydroentanglement treatment. The nozzle used in the hydroentanglement treatment was a nozzle with orifices having a hole diameter of 0.1 mm provided at intervals of 0.6 mm, and the interval between the nozzle and the fiber web during treatment was 20 mm.

[0109] Next, the fiber web after the hydroentanglement treatment was dried using a hot air penetration type heat treatment machine set at 135°C, and the fibers were thermally bonded to each other using the adhesive component of adhesive fiber A (high density polyethylene, sheath component) to obtain the laminated nonwoven fabric of Example 1.

[0110] Example 2 The laminated nonwoven fabric of Example 2 was obtained in the same manner as in Example 1, except that the water pressure of the water stream sprayed onto the surface of the second fibrous web and the water pressure of the water stream sprayed onto the surface of the first fibrous web were each 2.0 MPa.

[0111] Example 3 A laminated nonwoven fabric of Example 3 was obtained in the same manner as in Example 1, except that the first fibrous web was prepared by mixing 80 mass % of water-repellent cellulose fibers 1 and 20 mass % of hydrophilic cellulose fibers A.

[0112] Example 4 The laminated nonwoven fabric of Example 4 was obtained in the same manner as in Example 1, except that the second fiber web was prepared using only hydrophilic cellulose fiber A, and the fiber web after hydroentanglement was only subjected to a drying treatment using a hot air-penetrating type heat treatment machine set at 80°C.

[0113] Example 5 The laminated nonwoven fabric of Example 5 was obtained in the same manner as in Example 4, except that the second fibrous web was produced using only the hydrophilic cellulose fibers B.

[0114] Example 6 The laminated nonwoven fabric of Example 6 was obtained in the same manner as in Example 1, except that a second fiber web was prepared using adhesive fiber B instead of adhesive fiber A, and the fibers were bonded together using polybutylene succinate (sheath component) as the adhesive component.

[0115] Example 7 The laminated nonwoven fabric of Example 7 was obtained in the same manner as in Example 1, except that a second fiber web was prepared using adhesive fiber C instead of adhesive fiber A, and the fibers were bonded together using the high-density polyethylene that constitutes adhesive fiber C as an adhesive component.

[0116] Comparative Example 1 A laminated nonwoven fabric of Comparative Example 1 was obtained in the same manner as in Example 1, except that the first fibrous web was produced using only the hydrophilic cellulose fibers A.

[0117] Comparative Example 2 A laminated nonwoven fabric of Comparative Example 2 was obtained in the same manner as in Example 1, except that the first fibrous web was produced using only the water-repellent cellulose fibers 1.

[0118] Comparative Example 3 A laminated nonwoven fabric of Comparative Example 3 was obtained in the same manner as in Example 1, except that the first fibrous web was prepared by mixing 20% ​​by mass of water-repellent cellulose fibers 1 and 80% by mass of hydrophilic cellulose fibers A.

[0119] The nonwoven fabric was evaluated as follows. <Thickness of nonwoven fabric> The thickness of the nonwoven fabric was measured using a thickness gauge (THICKNESS GAUGE Model CR-60A (product name) manufactured by Daiei Scientific Instruments Co., Ltd.) while a load of 294 Pa or 1.96 kPa was applied to the nonwoven fabric.

[0120] <Strength and elongation> The strength and elongation were measured using a constant-speed tension tensile tester in accordance with JIS L 1913:2010 6.3, with a sample width of 5 cm, grip distance of 10 cm, and a tensile speed of 30±2 cm / min. The load at break (tensile strength), elongation, and stress at 10% elongation (force required to elongate by 10%) were measured. The tensile test was performed in the machine direction (MD) and cross direction (CD) of the nonwoven fabric as the tensile directions. The evaluation results are shown as the average of the values ​​measured for three samples. The tensile strength in dry (standard time, DRY) and wet (WET) conditions was measured.

[0121] <Coefficient of variation> The coefficient of variation was measured using a static and dynamic friction measuring instrument (Tribomaster TL201Ts, manufactured by Trinity Lab Co., Ltd.). A nonwoven fabric measuring 5 cm x 10 cm was prepared as a sample piece. The sample pieces were prepared with the MD and CD directions of the nonwoven fabric as their long sides. A tactile contactor (manufactured by Trinity Lab Co., Ltd.) was used as the contact terminal of the measuring instrument. 100 parts by mass of the sample piece was impregnated with 1000 parts by mass of distilled water, and the sample piece was fixed to the measuring table of the measuring instrument (table sliding type). The contact terminal was moved back and forth twice against the surface of the sample piece with a load of 30 gf, a speed of 10 mm / sec, and a distance of 30 mm. The value of the dynamic friction force in the second round trip was read, and the average value of the forward and backward values ​​was taken as the dynamic friction force (gf) of one sample piece.

[0122] Measurements were performed three times for each sample piece, and the average of a total of six measured values ​​in the MD and CD directions was taken as the kinetic friction force Fk (gf) for each Example and Comparative Example. The kinetic friction coefficient μk was calculated from the kinetic friction force Fk (gf) and the load (30 gf). In addition, the coefficient of variation (variation) CV of the kinetic friction coefficient was calculated from the standard deviation σ of the kinetic friction coefficient obtained during the measurement and the average value μk of the kinetic friction coefficient described above according to the following formula. The coefficient of variation CV was calculated for each of the surfaces of the first fiber layer and the second fiber layer. Coefficient of variation of dynamic friction coefficient (variation) CV=σ / μk

[0123] <Adhesion> To determine the adhesion, the moisture content after 15 minutes was first determined. A 5cm x 6cm sample piece (MD x CD) was prepared, the mass of the sample piece was measured, and then 100 parts by mass of the sample piece was impregnated with 1000 parts by mass of distilled water. The sample piece impregnated with distilled water was placed on a metal plate adjusted to 32°C, and the mass was measured after 15 minutes, and the moisture content after 15 minutes was calculated according to the following formula. Moisture content after 15 minutes (%)=[(m2-m1) / m1]×100 m1: Mass of the nonwoven fabric before it is soaked in distilled water (g) m2: Mass (g) of the nonwoven fabric after placing it on a metal plate at 32°C for 15 minutes

[0124] The adhesion force was measured using a static and dynamic friction measuring instrument (Tribomaster TL201Ts, manufactured by Trinity Labs, Inc.). A 12cm x 5cm specimen was prepared as a test piece taken from the same sample as the specimen for which the moisture content after 15 minutes was determined. The test pieces were prepared with the long sides in the MD and CD directions of the nonwoven fabric. An artificial skin (24cm long x 12cm wide, product name: BIO SKIN PLATE, manufactured and sold by Bealux, Inc.) was attached to the measurement table of the measuring instrument (table sliding type).

[0125] Based on the moisture content of each sample piece after 15 minutes, 100 parts by mass of the sample piece was impregnated with distilled water so that the moisture content was the same as the moisture content after 15 minutes. In this state, the end of the short side of the sample piece (this part is called the "clip end") was clamped with the clip of the measuring machine to hold it horizontally. The measurement table was moved so that only the area of ​​the sample with a long side of 8 cm and a short side of 5 cm from the end opposite the clip end (this part is called the "non-clipped end") overlapped with the artificial skin horizontally, and the sample was left for 15 minutes. The maximum resistance force (N) was read when the measurement table was moved parallel to the long side direction of the sample and in the direction away from the clip end at a speed of 10 mm / sec along the long side direction of the sample piece. For one example, measurements were made on three sample pieces in each of the MD and CD directions, and the average value of the maximum resistance forces (N) of a total of six pieces was calculated, and this was calculated based on the area of ​​the contact surface of the sample (40 cm 2 ) to obtain the adhesion strength per unit area (mN / cm2 ) was sought. In this example, the adhesive strength was measured on the surface of the first fiber layer, and the above measurement was carried out by bringing the surface of the first fiber layer into contact with the artificial skin.

[0126] <Water retention rate> The nonwoven fabric was cut into a size of 100mm x 100mm in the machine direction (MD) x cross direction (CD), the mass of the nonwoven fabric was measured, and then it was immersed in distilled water for 2 minutes. The nonwoven fabric soaked in distilled water was then hung by clamping three corners with clothespins, and the mass was measured after 10 minutes, and the water retention was calculated according to the following formula. The measurement was performed at a temperature of 23°C and a relative humidity of 55%. Water retention rate (%)=[(M2-M1) / M1]×100 M1: Mass of the nonwoven fabric before soaking in distilled water (g) M2: Mass of the nonwoven fabric after soaking in distilled water and hanging for 10 minutes (g)

[0127] The evaluation results of Examples 1 to 7 and Comparative Examples 1 to 3 are shown in Tables 1 to 3.

[0128] [Table 1]

[0129] [Table 2]

[0130] [Table 3]

[0131] In all the examples except for Example 4, the CV of the surface of the first fiber layer was smaller than that of the surface of the second fiber layer, and the surface of the first fiber layer had a smooth feel. In Example 4, the CV of the surface of the first fiber layer was larger than that of the second fiber layer, but the surface of the first fiber layer had a value equivalent to the CV of the other examples, and the surface of the first fiber layer had a smooth feel. In addition, in all the examples, the adhesion force of the surface of the first fiber layer was large. In Example 4, the CV of the surface of the second fiber layer was smaller than that of the first fiber layer, but when the surface of the second fiber layer was brought into contact with the skin, the first fiber layer was exposed to the outside and was prone to drying, and liquid was likely to move from the inner second fiber layer to the outer first fiber layer. As a result, the inconvenience of evaporation of the liquid to be supplied to the skin may occur.

[0132] In Comparative Example 1, the first fiber layer did not contain water-repellent cellulose fibers, so the adhesion was low and the water retention tended to be high. In Comparative Example 2, the first fiber layer was composed only of water-repellent cellulose fibers, so the mechanical strength (especially the tensile strength in the CD direction) was low and not practical. In Comparative Example 3, the proportion of water-repellent cellulose fibers in the first fiber layer was small, so the adhesion of the surface of the first fiber layer was low.

[0133] In Examples 4 and 5, the hydrophilic fibers in the second fiber layer were viscose rayon and solvent-spun cellulose fibers, respectively, and Example 5 exhibited greater tensile strength in the wet state and stress at 10% elongation than Example 4. This is believed to be because the solvent-spun cellulose fibers experience less loss in fiber strength when wet.

[0134] Examples 1, 6, and 7 are different in that the cross section of the adhesive fiber in the second fiber layer is a concentric core-sheath type (Examples 1 and 6) or a chrysanthemum-shaped split type (Example 7). Example 7 showed a higher water retention rate. This is thought to be because the split type composite fiber was split during the hydroentanglement treatment, increasing the surface area of ​​the fiber.

[0135] The present disclosure includes the following aspects. (Aspect 1) A laminated nonwoven fabric for a liquid-impregnated skin-applying sheet, comprising a first fiber layer and a second fiber layer laminated on the first fiber layer, the laminated nonwoven fabric comprising: the first fiber layer contains, based on the total mass of the first fiber layer, 30% by mass or more and 80% by mass or less of water-repellent cellulose fibers and 20% by mass or more and 70% by mass or less of hydrophilic cellulose fibers; the second fiber layer contains hydrophilic fibers in an amount of 50% by mass or more and water-repellent cellulosic fibers in an amount of 0% by mass or more and 20% by mass or less, based on the total mass of the second fiber layer; the first fiber layer and the second fiber layer are integrated by entanglement of the fibers, The first fiber layer is used by contacting it with the skin. Laminated nonwoven fabric for liquid-impregnated skin covering sheets. (Aspect 2) A laminated nonwoven fabric for a liquid-impregnated skin-applying sheet, comprising a first fiber layer and a second fiber layer laminated on the first fiber layer, the laminated nonwoven fabric comprising: the first fibrous layer comprises water-repellent cellulose fibers and hydrophilic cellulose fibers; the second fibrous layer comprises hydrophilic fibers; the first fiber layer and the second fiber layer are integrated by entanglement of the fibers, the spot absorptivity on the surface of the first fiber layer is 35% or more; the spot absorption time on the surface of the first fiber layer is 0.6 seconds or more; the spot absorption time on the surface of the second fiber layer is 0.1 seconds or less; The first fiber layer is used by contacting it with the skin. Laminated nonwoven fabric for liquid-impregnated skin covering sheets. (Aspect 3) 3. The liquid-impregnated laminated nonwoven fabric for a skin-covering sheet according to claim 1 or 2, wherein the second fiber layer contains 10% by mass or more and 30% by mass or less of adhesive fibers, based on the total mass of the second fiber layer, and the fibers are adhered to each other by the adhesive fibers. (Aspect 4) 4. The laminated nonwoven fabric for a liquid-impregnated skin application sheet according to any one of Aspects 1 to 3, wherein the hydrophilic fibers include hydrophilic cellulose fibers. (Aspect 5) 5. The laminated nonwoven fabric for a liquid-impregnated skin-application sheet according to aspect 4, comprising 85% by mass or more of cellulose fibers based on the total mass of the laminated nonwoven fabric. (Aspect 6) The basis weight of the laminated nonwoven fabric is 30 g / m 2 More than 80g / m 2 6. A liquid-impregnated laminated nonwoven fabric for use in a skin-application sheet according to any one of embodiments 1 to 5, which is as follows: (Aspect 7) preparing a first fiber web containing 30% by mass or more and 80% by mass or less of water-repellent cellulose fibers and 20% by mass or more and 70% by mass or less of hydrophilic cellulose fibers, based on the total mass of the first fiber web; preparing a second fiber web containing 50% by mass or more of hydrophilic fibers and 0% by mass or more and 20% by mass or less of water-repellent cellulosic fibers based on the total mass of the second fiber web; overlapping the first fiber web and the second fiber web to produce a laminated fiber web; subjecting the laminated fiber web to an entanglement treatment using a high-pressure fluid flow to entangle the fibers. Including, A method for producing a laminated nonwoven fabric for a liquid-impregnated skin covering sheet, in which the first fiber web becomes a first fiber layer and the second fiber web becomes a second fiber layer, and the first fiber layer is used by contacting the skin. (Aspect 8) A method for producing a laminated nonwoven fabric for a liquid-impregnated skin application sheet according to aspect 7, wherein the laminated web is a two-layered web consisting of the first fiber web and the second fiber web, and in the entanglement treatment using the high-pressure fluid stream, the high-pressure fluid stream is a water stream, and the water stream is first sprayed onto a surface of the second fiber web, and then the water stream is sprayed onto a surface of the first fiber web. (Aspect 9) A liquid-impregnated skin application sheet, comprising 100 parts by mass of the liquid-impregnated laminated nonwoven fabric for a skin application sheet according to any one of the first to sixth aspects, impregnated with a liquid in an amount of 500 parts by mass or more and 2000 parts by mass or less. (Aspect 10) A face mask obtained by impregnating 500 parts by mass or more and 2000 parts by mass or less of liquid with respect to 100 parts by mass of the liquid-impregnated laminated nonwoven fabric for a skin application sheet according to any one of the first to sixth aspects. [Industrial Applicability]

[0136] The laminated nonwoven fabric of the present disclosure is formed by integrating a first fiber layer containing water-repellent cellulose fibers and hydrophilic cellulose fibers with a second fiber layer containing hydrophilic cellulose fibers and no water-repellent cellulose fibers or containing 20 mass% or less of water-repellent cellulose fibers, and the first fiber layer exhibits good adhesion to the skin in a wet state. Therefore, the laminated nonwoven fabric of the present disclosure is useful as a substrate for covering the skin in a liquid-impregnated state, such as a face mask.

Claims

1. A laminated nonwoven fabric for a liquid-impregnated skin-applying sheet, comprising a first fiber layer and a second fiber layer laminated on the first fiber layer, the laminated nonwoven fabric comprising: the first fiber layer contains, based on the total mass of the first fiber layer, 30% by mass or more and 80% by mass or less of water-repellent cellulose fibers and 20% by mass or more and 70% by mass or less of hydrophilic cellulose fibers; the second fiber layer contains hydrophilic fibers in an amount of 50% by mass or more and water-repellent cellulosic fibers in an amount of 0% by mass or more and 20% by mass or less, based on the total mass of the second fiber layer; the first fiber layer and the second fiber layer are integrated by entanglement of the fibers, The water-repellent cellulose fiber is one or more selected from regenerated fibers, cellulose fibers obtained by a melt spinning method, and semi-synthetic fibers, and has a fiber length of 28 mm or more; The first fiber layer is used by contacting it with the skin. Laminated nonwoven fabric for liquid-impregnated skin covering sheets.

2. A laminated nonwoven fabric for a liquid-impregnated skin-applying sheet, comprising a first fiber layer and a second fiber layer laminated on the first fiber layer, the laminated nonwoven fabric comprising: the first fibrous layer comprises water-repellent cellulose fibers and hydrophilic cellulose fibers; the second fibrous layer comprises hydrophilic fibers; the first fiber layer and the second fiber layer are integrated by entanglement of the fibers, the spot absorption rate on the surface of the first fiber layer is 35% or more; a spot absorption time on the surface of the first fiber layer is 0.6 seconds or more; a spot absorption time on the surface of the second fiber layer is 0.1 seconds or less; The water-repellent cellulose fiber is one or more selected from regenerated fibers, cellulose fibers obtained by a melt spinning method, and semi-synthetic fibers, and has a fiber length of 28 mm or more; The first fiber layer is used by contacting it with the skin. Laminated nonwoven fabric for liquid-impregnated skin covering sheets.

3. 3. The laminated nonwoven fabric for a liquid-impregnated skin covering sheet according to claim 1 or 2, wherein the second fiber layer contains 10% by mass or more and 30% by mass or less of adhesive fibers based on the total mass of the second fiber layer, and the fibers are bonded to each other by the adhesive fibers.

4. A laminated nonwoven fabric for a liquid-impregnated skin-applying sheet, comprising a first fiber layer and a second fiber layer laminated on the first fiber layer, the laminated nonwoven fabric comprising: the first fiber layer contains, based on the total mass of the first fiber layer, 30% by mass or more and 80% by mass or less of water-repellent cellulose fibers and 20% by mass or more and 70% by mass or less of hydrophilic cellulose fibers; the second fiber layer contains hydrophilic fibers in an amount of 50% by mass or more and water-repellent cellulosic fibers in an amount of 0% by mass or more and 20% by mass or less, based on the total mass of the second fiber layer; the first fiber layer and the second fiber layer are integrated by entanglement of the fibers, the second fiber layer contains adhesive fibers in an amount of 10% by mass or more and 30% by mass or less based on the total mass of the second fiber layer, and fibers are bonded to each other by the adhesive fibers; The first fiber layer is used by contacting it with the skin. Laminated nonwoven fabric for liquid-impregnated skin covering sheets.

5. A laminated nonwoven fabric for a liquid-impregnated skin-applying sheet, comprising a first fiber layer and a second fiber layer laminated on the first fiber layer, the laminated nonwoven fabric comprising: the first fibrous layer comprises water-repellent cellulose fibers and hydrophilic cellulose fibers; the second fibrous layer comprises hydrophilic fibers; the first fiber layer and the second fiber layer are integrated by entanglement of the fibers, the spot absorption rate on the surface of the first fiber layer is 35% or more; a spot absorption time on the surface of the first fiber layer is 0.6 seconds or more; a spot absorption time on the surface of the second fiber layer is 0.1 seconds or less; the second fiber layer contains adhesive fibers in an amount of 10% by mass or more and 30% by mass or less based on the total mass of the second fiber layer, and fibers are bonded to each other by the adhesive fibers; The first fiber layer is used by contacting it with the skin. Laminated nonwoven fabric for liquid-impregnated skin covering sheets.

6. 6. The laminated nonwoven fabric for a liquid-impregnated skin application sheet according to claim 1, wherein the hydrophilic fibers include hydrophilic cellulose fibers.

7. 7. The laminated nonwoven fabric for a liquid-impregnated skin application sheet according to claim 6, comprising 85% by mass or more of cellulose fibers based on the total mass of the laminated nonwoven fabric.

8. The basis weight of the laminated nonwoven fabric is 30 g / m 2 80g / m or more 2 The laminated nonwoven fabric for a liquid-impregnated skin application sheet according to any one of claims 1 to 7, wherein:

9. preparing a first fiber web containing 30% by mass or more and 80% by mass or less of water-repellent cellulose fibers and 20% by mass or more and 70% by mass or less of hydrophilic cellulose fibers, based on the total mass of the first fiber web; preparing a second fiber web containing 50% by mass or more of hydrophilic fibers and 0% by mass or more and 20% by mass or less of water-repellent cellulose fibers, based on the total mass of the second fiber web; overlapping the first fiber web and the second fiber web to produce a laminated fiber web; subjecting the laminated fiber web to an entanglement treatment using a high-pressure fluid flow to entangle the fibers. Including, The laminated web is a two-layered web consisting of the first fiber web and the second fiber web, and the entanglement treatment using the high-pressure fluid flow is a water flow, and the water flow is first sprayed onto a surface of the second fiber web, and then sprayed onto a surface of the first fiber web, A method for producing a laminated nonwoven fabric for a liquid-impregnated skin covering sheet, in which the first fiber web becomes a first fiber layer and the second fiber web becomes a second fiber layer, and the first fiber layer is used by contacting the skin.

10. preparing a first fiber web containing 30% by mass or more and 80% by mass or less of water-repellent cellulose fibers and 20% by mass or more and 70% by mass or less of hydrophilic cellulose fibers, based on the total mass of the first fiber web; preparing a second fiber web containing 50% by mass or more of hydrophilic fibers and 0% by mass or more and 20% by mass or less of water-repellent cellulose fibers, based on the total mass of the second fiber web; overlapping the first fiber web and the second fiber web to produce a laminated fiber web; subjecting the laminated fiber web to an entanglement treatment using a high-pressure fluid flow to entangle the fibers. Including, The water-repellent cellulose fiber is one or more selected from regenerated fibers, cellulose fibers obtained by a melt spinning method, and semi-synthetic fibers, and has a fiber length of 28 mm or more; A method for producing a laminated nonwoven fabric for a liquid-impregnated skin covering sheet, in which the first fiber web becomes a first fiber layer and the second fiber web becomes a second fiber layer, and the first fiber layer is used by contacting the skin.

11. preparing a first fiber web containing 30% by mass or more and 80% by mass or less of water-repellent cellulose fibers and 20% by mass or more and 70% by mass or less of hydrophilic cellulose fibers, based on the total mass of the first fiber web; preparing a second fiber web containing 50% by mass or more of hydrophilic fibers and 0% by mass or more and 20% by mass or less of water-repellent cellulose fibers, based on the total mass of the second fiber web; overlapping the first fiber web and the second fiber web to produce a laminated fiber web; subjecting the laminated fiber web to an entanglement treatment using a high-pressure fluid flow to entangle the fibers. Including, The second fiber web contains 10% by mass or more and 30% by mass or less of adhesive fibers based on the total mass of the second fiber web, and further includes bonding the fibers to each other with the adhesive fibers after the entanglement treatment, A method for producing a laminated nonwoven fabric for a liquid-impregnated skin covering sheet, in which the first fiber web becomes a first fiber layer and the second fiber web becomes a second fiber layer, and the first fiber layer is used by contacting the skin.

12. 12. The method for producing a laminated nonwoven fabric for a liquid-impregnated skin application sheet according to claim 10 or 11, wherein the laminated web is a two-layered web consisting of the first fiber web and the second fiber web, and in the entanglement treatment using the high-pressure fluid flow, the high-pressure fluid flow is a water flow, and the water flow is first sprayed onto a surface of the second fiber web, and then the water flow is sprayed onto a surface of the first fiber web.

13. A liquid-impregnated skin application sheet, comprising: a laminated nonwoven fabric for a liquid-impregnated skin application sheet, the laminated nonwoven fabric being impregnated with a liquid in an amount of 500 parts by mass or more and 2000 parts by mass or less per 100 parts by mass of the laminated nonwoven fabric for a liquid-impregnated skin application sheet; The liquid-impregnated laminated nonwoven fabric for a skin-covering sheet is A laminated nonwoven fabric comprising a first fiber layer and a second fiber layer laminated on the first fiber layer, the second fiber layer being integrated with the first fiber layer, the first fiber layer contains, based on the total mass of the first fiber layer, 30% by mass or more and 80% by mass or less of water-repellent cellulose fibers and 20% by mass or more and 70% by mass or less of hydrophilic cellulose fibers; the second fiber layer contains hydrophilic fibers in an amount of 50% by mass or more and water-repellent cellulosic fibers in an amount of 0% by mass or more and 20% by mass or less, based on the total mass of the second fiber layer; the first fiber layer and the second fiber layer are integrated by entanglement of the fibers, The first fiber layer is used by contacting it with the skin. A liquid-impregnated skin covering sheet which is a laminated nonwoven fabric.

14. A liquid-impregnated skin application sheet, comprising: a laminated nonwoven fabric for a liquid-impregnated skin application sheet, the laminated nonwoven fabric being impregnated with a liquid in an amount of 500 parts by mass or more and 2000 parts by mass or less per 100 parts by mass of the laminated nonwoven fabric for a liquid-impregnated skin application sheet; The liquid-impregnated laminated nonwoven fabric for a skin-covering sheet is A laminated nonwoven fabric comprising a first fiber layer and a second fiber layer laminated on the first fiber layer, the second fiber layer being integrated with the first fiber layer, the first fibrous layer comprises water-repellent cellulose fibers and hydrophilic cellulose fibers; the second fibrous layer comprises hydrophilic fibers; the first fiber layer and the second fiber layer are integrated by entanglement of the fibers, the spot absorption rate on the surface of the first fiber layer is 35% or more; a spot absorption time on the surface of the first fiber layer is 0.6 seconds or more; a spot absorption time on the surface of the second fiber layer is 0.1 seconds or less; The first fiber layer is used by contacting it with the skin. A liquid-impregnated skin covering sheet which is a laminated nonwoven fabric.

15. 15. The liquid-impregnated skin application sheet according to claim 13 or 14, which is a face mask.

16. A liquid-impregnated skin application sheet, comprising 100 parts by mass of the liquid-impregnated laminated nonwoven fabric for a skin application sheet according to any one of claims 1 to 8, and impregnated with a liquid in an amount of 500 parts by mass to 2000 parts by mass.

17. A face mask obtained by impregnating 500 parts by mass or more and 2000 parts by mass or less of liquid with respect to 100 parts by mass of the liquid-impregnated laminated nonwoven fabric for skin application sheet according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Composite non-woven fabric and its production

    JP1997132847A

  • Hydrolyzable absorbent article

    JP2004344443A

  • Nonwoven fabric for fluid impregnated skin coating sheet and fluid impregnated skin coating sheet

    JP2016098464A

  • Surface sheet for absorbent article, method for manufacturing the same, and absorbent article

    JP2020178823A

  • Non-woven fabrics containing cotton

    JP3211439U